Comunicação organizacional e participação: análise do engajamento interno em políticas estratégicas de uma universidade pública federal - Araújo, Ana Carolina (2018)
This research had the purpose of investigating how the organizational communication of a public university can contribute to the engagement of the internal public (students, teachers and technical-administrative staff), with a view to stimulating their involvement in the process of building institutional strategies. With reference to the approaches on subjects like Communication; Organizational communication; Public Communication; and Participation, among others, developed a theoretical framework capable of pointing out ways to understand the importance of organizational communication in the involvement of the internal community in policies that define the institution's future, such as Institutional Self-Assessment and the Institutional Development Plan. The work was based on a case study, whose methodological course involved two different data collection techniques such as documentary research and semi-structured interviews with the students and servers that integrate the Federal University of Alfenas - UNIFAL-MG, campus headquartersion. The interviews were structured in order to allow the analysis of the communication channels used by the university and to verify the knowledge of the internal public about the necessity of their participation. This method also made it possible to identify under what conditions the internal public has an interest to contribute with suggestions in the construction of institutional strategies. The data processing technique was the content analysis, whose applicability is marked by a great disparity of forms and adaptable to the vast field of communications. It is believed that this research will contribute to open new paths in the construction of institutional policies, with communication as an instrument that allows the participation of the internal public in the planning of strategic actions to be expanded. It is expected that from an effective involvement of the academic community, it will be possible to develop actions based on the needs of the group and, consequently, to promote better management results.